Atmospheric pollen dynamics in Malaga (s. Spain) during 2013-2014. Seasonal trends - Recio-Criado, María Marta; Picornell Rodríguez, Antonio; Gharbi, Dorra; Lozano-Torelli, Inmaculada; Ruiz, Salvador; Cabezudo-Artero, Baltasar; Trigo-Pérez, María del Mar (My University, 2015)
In this work we present the atmospheric pollen results obtained in Malaga, a coastal Mediterranean city situated in southern Spain, throughout 2013 and 2014. The main objective is to compare the results obtained these years with those registered during the 21 previous years (1992-2012) and detect possible significant trends. The samplings were made with the aid of a Hirst-type volumetric pollen trap (Hirst, 1952) situated on the roof of the building of the Faculty of Sciences, Campus de Teatinos. The mounting of the samples and the pollen counting were according to the methodology proposed by the Spanish Aerobiology Network, the REA (Galán et al., 2007). In this work, the seasonal evolution of the different taxa, annual pollen index and features of the main pollen season (length and start, end and peak days) are studied and the results obtained in 2013 and 2014 are compared to the average values of the previous years in order to detect differences related to climate change. The annual mean temperature have been rising in 2013 and 2014 (19.1 and 19.9ºC) comparing to the average of the last 20 years (18.7ºC). The annual total rainfall have been declining in 2013 and 2014 (354.7 and 373.1 mm) comparing to the average of the last 20 years (546.2 mm). The relative humidity declined in 2014 (60.6%) compared to last 20 years (66.6%). Among the significant trends that we have observed are: increase in the annual pollen index of Quercus and Olea, decrease in the annual pollen index of Chenopodiaceae, Plantago and Cyperaceae, delay in the end and increase in the length of the main pollen season of Quercus, delay and reduction in the length of the main pollen season of Gramineae pollen.
Keywords: Palinología; Clima - Cambios; Pollen; Aerobiology; Allergy; Phenology; Climatic change; Meteorology